2021
DOI: 10.1155/2021/8810279
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Classification for Crop-Type Mapping Using the Fusion of High-Resolution Satellite Imagery in a Semiarid Area

Abstract: The monitoring of cultivated crops and the types of different land covers is a relevant environmental and economic issue for agricultural lands management and crop yield prediction. In this context, this paper aims to use and evaluate the contribution of multisensors classification based on machine learning classifiers to crop-type identification in a semiarid area of Morocco. It is a very heterogeneous zone characterized by mixed crops (tree crops with annual crops, same crop with different phenological state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…Various studies have shown the potential to map crop types based on Sentinel-1 time series without additional optical data input in Europe (e.g., [30][31][32][33][34][35][36][37][38][39][40][41]) and in Germany (e.g., [42][43][44]). However, particularly promising are approaches combining optical and SAR data (e.g., for Asia [45], Africa [46,47], Europe [48][49][50][51][52][53][54][55], and Germany [56][57][58]). Such synergistic approaches consistently showed better overall accuracies than monosensor classifications (e.g., [48,51,56,57]), particularly in the case of challenging cloud situations [49].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the potential to map crop types based on Sentinel-1 time series without additional optical data input in Europe (e.g., [30][31][32][33][34][35][36][37][38][39][40][41]) and in Germany (e.g., [42][43][44]). However, particularly promising are approaches combining optical and SAR data (e.g., for Asia [45], Africa [46,47], Europe [48][49][50][51][52][53][54][55], and Germany [56][57][58]). Such synergistic approaches consistently showed better overall accuracies than monosensor classifications (e.g., [48,51,56,57]), particularly in the case of challenging cloud situations [49].…”
Section: Introductionmentioning
confidence: 99%
“…Even in well-developed and well-organised countries, ground-based crop area estimates are often not available until a few months after harvest [39]. Obtaining a reliable figure before harvest is a major challenge and, at the same time, vital for the formulation of policymaking and decision-making [39,59]. Figure 2 shows the processing steps typically applied to remote sensing data to predict crop type.…”
Section: Identifying and Estimating Crop Areamentioning
confidence: 99%
“…Compared to a humid environment, ASA regions typically have specific climatic and regional characteristics which pose many challenges to accurately identifying and estimating crop area [39,59]. Due to considerable changes in the spatial and temporal distribution of rainfall, and the fact that the majority of smallholder farms in ASA regions rely on rainfall to start planting, identifying and estimating crop area can be difficult [39].…”
Section: Identifying and Estimating Crop Areamentioning
confidence: 99%
“…Apart from temporal data requirements, crop mapping and identification demands robust algorithms that are sensitive to the spectral and temporal information of the multispectral data [17][18][19][20]. Different computer vision techniques have been applied depending upon the application in the field of agriculture.…”
Section: Introductionmentioning
confidence: 99%